Comparative study the effectiveness 4D autodesk naviswork software with traditional software planner - Nurul 'Amirah, Khalil (2017)
Construction industry is the one of the key economic development activities in Malaysia. Before starting any construction, all developer, contractor, and consultant desire a project to run smoothly without any arising problem. However, there are almost same arising problem in most countries including Malaysia. Basically, these problems arise through work program implementation including the clash either between beam and column or wall and beam. These problems contribute to the delay of construction project since it takes a long time to settle the arising problems. For example, a project at United Kingdom of America was to build National Health Service Care where this project was delay because of poor planned. The poor planning of this project cause the budget run. Original budget was $4.68 billion, but when this problem happen this budget subsequently grown to $24 billion, with some observers estimating it could grow to as much as $40B. This project taking 4 years to finish up all the thing. Therefore, an alternative study had been explored to minimize the construction problems before the construction work commences. This study focused on the effectiveness planning in real construction project by using Naviswork. A few related data had been obtained from a real construction data consisting of a structural, architectural drawing, and detailed work program of the project. These drawings were developed into 3D model by using Revit software, followed with the clash detection between these models by using Naviswork. In order to check the sequence of work program, the work program had been attached into Microsoft Project, meanwhile the structural and architectural model into Naviswork. There was about 257 clashes detection between structural and architectural model. Meanwhile, a problem had been detected starting from day 373 week 54 in date 17 July 2015 through the work program simulation where the architectural model started to overtake the structural model. Once the result had been obtained, these problems need to be solved before the project commences. From this simulation, it could be concluded that there was weakness through the traditional project planning since it did not detect the problem immediately. In conclusion, all construction project should take the initiative to decrease the problem prior starting the construction work in order so that the project can run smoothly.